Możliwości zastosowania metody statystycznej do badania autobiografii - Suchocki, Bolesław; Szafran, Aurelia; Wawruch, Krzysztof (Wydział Prawa i Administracji UAM, 1987)
The article presents the proposal to apply the statistical method to analysing autobiographical materials coming from memoirs competitions. The authors offer the way of dealing with basic issues conditioning the possibility of applying statistics to such materials, i.e. 1) precise defining the collectivity being the subject of examination, 2) defining the traits (of individuals) relevant for a researcher, 3) defining the level of measurement of traits relevant for a researcher, 4) counting the number of individuals with particular traits or particular level of their intensity.
Possibilities of applying the statistical method to examining autobiographies